Pengaruh Employee Branding Perusahaan terhadap Employer Branding - Hariyono, Ramadhan Devo; Ambarwati, Mega Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study investigates the impact of employer branding on job application interest and employee retention in contemporary organizational settings. Employer branding is conceptualized as a strategic mechanism for shaping an organization’s image as an attractive and competitive workplace. Employing a quantitative research design and multiple linear regression analysis, data were collected from 220 respondents, including job seekers and active employees across various industries. The findings reveal that employer branding significantly and positively influences both dependent variables, both individually and jointly. These results reinforce the argument that organizational image both internally and externally serves as a critical determinant in individuals’ decisions to apply for a position or remain in employment. This study contributes to the literature on human resource management and corporate communication while offering strategic insights for organizations seeking to enhance talent attraction and retention through employer brand development.